Composite separator, secondary battery, and electric device

CN119768964APending Publication Date: 2025-04-04CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380056589.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the charging and discharging process of existing secondary batteries, side reactions between metals and electrolytes seriously affect the stability of the interface, resulting in a decrease in electrochemical performance and safety performance, and cannot meet the application needs of the new generation of electrochemical systems.

Method used

A composite isolation membrane containing a polymer coating is used. By setting a polymer coating with high sodium ion conductivity on one side of the isolation membrane substrate, the contact between the metal and the electrolyte is reduced, the sodium ion transmission mode is changed, and side reactions are reduced. And the mechanical strength and wettability of the membrane are improved through surface-active additives and reinforcing components.

Benefits of technology

It effectively improves the cycle performance and storage performance of secondary batteries, reduces side reactions, extends the service life of the battery, and expands its application scope.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768964A_ABST
    Figure CN119768964A_ABST
Patent Text Reader

Abstract

The invention provides a composite isolating membrane, a secondary battery and an electric device. The composite isolating membrane comprises an isolating membrane base material and a polymer coating located on one side of the isolating membrane base material, and the sodium ion conductivity of the composite isolating membrane is 0.3 mS / cm to 1 mS / cm. The polymer coating is beneficial to reducing the contact between metal deposited on the current collector and electrolyte, so that the side reaction between the metal and the electrolyte is reduced, and the cycle performance and the storage performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Composite separator, secondary battery and electrical device Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite isolation membrane, a secondary battery, and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.

[0003] Interface stability is an important indicator for measuring secondary batteries. Side reactions between the electrode and the electrolyte will seriously affect the stability of the interface, resulting in a decline in the battery's electrochemical performance and safety performance, and unable to meet the application needs of the new generation of electrochemical systems.

[0004] Summary of the Invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a composite isolation membrane comprising a polymer coating, which is beneficial to reduce the contact between the metal deposited on the current collector and the electrolyte, thereby reducing the side reactions between the metal and the electrolyte and improving the cycle performance and storage performance of the battery.

[0006] In a first aspect of the present application, a composite isolation membrane is provided, comprising an isolation membrane substrate and a polymer coating located on one side of the isolation membrane substrate. The sodium ion conductivity of the composite isolation membrane is 0.3 mS / cm to 1 mS / cm.

[0007] By providing a polymer coating with high sodium ion conductivity on one side of the separator substrate, the sodium metal phase in the negative electrode can be effectively protected, the side reactions between the electrolyte and the metal can be reduced, and the battery's cycling and storage performance can be improved. On the one hand, the polymer coating with high sodium ion conductivity can effectively change the way sodium ions are transferred between the electrolyte and the electrode, reducing the free electrolyte solvent on the surface of the electrode through solid-phase transfer, thereby reducing the side reactions between the electrolyte and the electrode. On the other hand, the polymer coating is elastically compressed and covered on the surface of the electrode during the battery assembly process. Under the action of mechanical force, the contact between the sodium metal phase in the negative electrode and the electrolyte is further reduced, protecting the sodium metal phase and improving the battery's cycling and storage performance.

[0008] In any embodiment, the polymer coating comprises at least one of a polymer containing sodium carboxylate groups and / or sodium sulfonate groups, the polymer being conductive to metallic sodium ions.

[0009] Polymers containing sodium carboxylate groups and / or sodium sulfonate groups can conduct sodium ions, and polymer coatings containing sodium carboxylate groups and / or sodium sulfonate groups can remove solvents from the solvated sodium ions during the sodium ion conduction process, thereby reducing the free electrolyte solvent on the interface between the sodium metal and the isolation membrane, thereby reducing the side reaction between the electrolyte and metallic sodium, and improving the cycle performance and storage performance of the battery.

[0010] In any embodiment, the polymer includes one or more of sodium carboxymethyl cellulose, sodium polyacrylate, sodium alginate, sodium perfluorosulfonic acid resin, sodium polymethacrylate and sodium polystyrene sulfonate, and optionally includes one or more of sodium carboxymethyl cellulose and sodium alginate.

[0011] Polymer coatings containing the aforementioned polymers all exhibit high sodium ion conductivity. By altering the solvation structure of sodium ions in the electrolyte, they reduce the amount of free electrolyte solvent at the interface between sodium metal and the separator, thereby minimizing side reactions between the electrolyte and sodium metal and improving the battery's cycling and storage performance. Polymers containing sodium carboxymethyl cellulose or sodium alginate can further enhance the battery's cycling and storage performance.

[0012] In any embodiment, the thickness of the polymer coating is 15 nm to 1500 nm, optionally 50 nm to 1000 nm.

[0013] Controlling the polymer coating thickness to 15nm to 1500nm can both avoid or reduce the inadequate protection of the sodium metal phase in the negative electrode due to a thin coating, and also avoid or reduce the adverse effects of an increase in battery internal resistance due to an excessively thick coating. Further controlling the polymer coating thickness to 50nm to 1000nm can further improve the battery's cycling and storage performance.

[0014] In any embodiment, the polymer coating further comprises a surfactant additive, wherein the surfactant additive comprises one or more of sodium lauryl sulfate, sodium polydipropylene sulfonate and polyethylene glycol, and optionally sodium polydipropylene sulfonate.

[0015] The addition of surface additives is beneficial to improving the wettability between the polymer coating and sodium metal, so that sodium ions can be more evenly deposited on the surface of the negative electrode current collector, reducing the generation of sodium dendrites and avoiding internal short circuits in the battery. It is also beneficial to improving the cycle performance and storage performance of sodium metal batteries.

[0016] In any embodiment, based on the total mass of the polymer coating, the mass content of the surfactant additive is 0.05% to 5%, optionally 0.2% to 3%.

[0017] Controlling the surfactant content to 0.05% to 5% can avoid or reduce the technical effect of not improving the wettability between the polymer coating and the sodium metal due to a low surfactant content, and can also avoid or reduce the increase in battery impedance and the resulting decrease in battery performance due to a high surfactant content. Further controlling the surfactant content to 0.2% to 3% can further improve the battery's cycling and storage performance.

[0018] In any embodiment, the polymer coating further comprises a reinforcing component comprising one or more of polyvinylidene fluoride, styrene-butadiene copolymer, polyimide, polyacrylonitrile, polyacrylamide, polymethyl methacrylate, nitrile rubber and polyurethane, optionally comprising styrene-butadiene copolymer.

[0019] Adding reinforcing components to the polymer coating is beneficial to improving the mechanical strength and flexibility of the composite diaphragm membrane and expanding the application of the composite isolation membrane.

[0020] In any embodiment, based on the total mass of the polymer coating, the mass content of the reinforcing component is 0.01% to 50%, optionally 0.05% to 10%.

[0021] Controlling the weight content of the reinforcing component to 0.01% to 50% can avoid or reduce the inability to improve the performance of the composite separator due to a low weight content of the reinforcing component, and can also avoid or reduce the increase in battery impedance and the resulting decrease in battery performance due to a high weight content of the reinforcing component. Further controlling the weight content of the reinforcing component to 0.05% to 10% can further improve the cycling performance and storage performance of the battery.

[0022] In any embodiment, the separator substrate comprises one or more of polyethylene, polypropylene, polyester, cellulose, polyimide, polyamide, spandex fiber and aramid fiber, and optionally comprises polyethylene.

[0023] The sources of isolation membrane substrates are wide, and all of the above isolation membrane substrates can be used in combination with polymer coatings to improve battery performance.

[0024] A second aspect of the present application provides a secondary battery comprising a negative electrode plate, an electrolyte, and the composite separator described in the first aspect, wherein the polymer coating is located on the negative electrode plate side.

[0025] The composite isolation membrane located on the side of the polymer negative electrode plate can effectively protect the sodium metal phase in the negative electrode plate, reduce the side reaction between the electrolyte and metallic sodium, and improve the electrochemical performance of the battery.

[0026] In any embodiment, the secondary battery is a negative electrode-less sodium secondary battery.

[0027] In any embodiment, the electrolyte includes an ether solvent, and the ether solvent includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyltetrahydrofuran, diphenyl ether and crown ether, and optionally includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0028] Ether solvents possess superior molecular anti-reduction properties, promoting the formation of a stable solid electrolyte interface on the sodium metal surface and reducing side reactions during battery cycling. The combination of a composite separator and an ether solvent simultaneously protects the sodium metal phase in the negative electrode through the polymer coating and stabilizes the formation of a solid electrolyte interface, significantly reducing side reactions and improving battery performance. Ether solvents including one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether can further enhance the battery's cycling and storage performance.

[0029] In any embodiment, the negative electrode plate includes a negative electrode current collector and a primer layer provided on at least one surface of the negative electrode current collector, wherein the primer layer includes one or more of carbon nanotubes, graphite, graphene, silver composite carbon nanoparticles, and tin composite carbon nanoparticles.

[0030] The above-mentioned primer layer not only has excellent conductivity, but also facilitates the uniform deposition of metal ions on the surface of the current collector, thereby improving the coulombic efficiency and cycle performance of the battery.

[0031] In any embodiment, the surface density of the primer layer is 0.5 g / m 2 ~35g / m 2 .

[0032] Surface density is 0.5g / m 2 ~35g / m 2 The bottom coating is beneficial to the uniform distribution of nucleation sites in the negative electrode-free secondary battery, promoting the uniform deposition of metals without affecting the electron transport behavior.

[0033] In any embodiment, the primer layer has a thickness of 0.2 μm to 50 μm.

[0034] Controlling the thickness of the bottom coating layer to be 0.2 μm to 50 μm can provide enough nucleation sites for the negative electrode-free secondary battery, which is beneficial to the uniform deposition of metal ions and inhibits dendrites.

[0035] A third aspect of the present application provides an electrical device comprising the secondary battery according to the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0037] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;

[0038] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application;

[0039] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0040] FIG5 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG4 ;

[0041] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0042] Explanation of reference numerals: 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION

[0043] Below, embodiments of the composite separator, secondary battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0044] " scope " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and selected lower limit and upper limit define the boundary of special scope. The scope that this mode limits can be to include end value or not include end value, and can be arbitrarily combined, and promptly any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 listed, and if the maximum range value 3,4 and 5 are listed, then the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0047] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0048] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0049] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0050] Metal secondary batteries are secondary batteries that use a metal material (such as lithium, sodium, magnesium, potassium, and other metals) as the negative electrode. The metal material on the negative electrode current collector can be pre-deposited on the current collector surface as the negative electrode active material, or it can be deposited in situ during the charge and discharge process. This means that metal secondary batteries include sodium batteries, lithium batteries, magnesium batteries, potassium batteries, and other batteries with negative electrode active materials, as well as batteries without negative electrodes. In negative electrode-free batteries, the negative electrode sheet uses a negative electrode current collector and does not contain negative electrode active materials. During the initial charge and discharge process, metal ions are deposited in situ on the negative electrode current collector.

[0051] There are currently many problems with metal batteries. Taking the negative electrode-free sodium battery as an example, during the charging and discharging process, side reactions are likely to occur between metallic sodium and the electrolyte, consuming a large amount of sodium elements and reducing the battery's cycle performance and storage performance.

[0052] [Composite isolation film]

[0053] Based on this, the present application proposes a composite isolation membrane comprising an isolation membrane substrate and a polymer coating located on one side of the isolation membrane substrate. The sodium ion conductivity of the composite isolation membrane is 0.3 mS / cm to 1 mS / cm.

[0054] The polymer coating protects the sodium metal by reducing the contact between the sodium metal and the electrolyte, thereby reducing the side reactions between the sodium metal and the electrolyte. The polymer coating is located between the negative electrode and the separator substrate, and the polymer coating can conduct metal ions. During charging, the sodium metal ions diffuse from the positive electrode to the negative electrode, and are deposited on the negative electrode current collector or the negative electrode bottom coating through the polymer coating. During discharge, the sodium metal loses electrons and desorbs from the negative electrode in the form of sodium metal ions, which are then conducted through the polymer coating to diffuse toward the positive electrode.

[0055] Herein, the term "one side of the separator substrate" refers to the side of the surface of the separator substrate.

[0056] By providing a polymer coating with high sodium ion conductivity on one side of the separator substrate, the sodium metal phase in the negative electrode can be effectively protected, the side reactions between the electrolyte and the metal can be reduced, and the battery's cycling and storage performance can be improved. On the one hand, the polymer coating with high sodium ion conductivity can effectively change the way sodium ions are transferred between the electrolyte and the electrode, reducing the free electrolyte solvent on the surface of the electrode through solid-phase transfer, thereby reducing the side reactions between the electrolyte and the electrode. On the other hand, the polymer coating is elastically compressed and covered on the surface of the electrode during the battery assembly process. Under the action of mechanical force, the contact between the sodium metal phase in the negative electrode and the electrolyte is further reduced, protecting the sodium metal phase and improving the battery's cycling and storage performance.

[0057] In some embodiments, the polymer coating is in direct contact with the surface of the release film substrate.

[0058] In some embodiments, the polymer coating and the barrier film substrate have one or more coating layers.

[0059] In some embodiments, the polymer coating includes at least one polymer containing sodium carboxylate groups and / or sodium sulfonate groups, which polymer is conductive to metallic sodium ions.

[0060] In some embodiments, the polymer coating comprises a polymer comprising sodium carboxylate groups.

[0061] In some embodiments, the polymer coating comprises a polymer comprising sodium sulfonate groups.

[0062] In some embodiments, the polymer coating comprises a polymer comprising sodium carboxylate groups and sodium sulfonate groups.

[0063] Polymers containing sodium carboxylate groups and / or sodium sulfonate groups can conduct sodium ions, and polymer coatings containing sodium carboxylate groups and / or sodium sulfonate groups can change the solvation structure of sodium ions in the electrolyte, reduce the free electrolyte solvent at the interface between sodium metal and the isolation membrane, thereby reducing the side reaction between the electrolyte and metallic sodium, and improving the cycle performance and storage performance of the battery.

[0064] In some embodiments, the polymer includes one or more of sodium carboxymethyl cellulose, sodium polyacrylate, sodium alginate, sodium perfluorosulfonic acid resin, sodium polymethacrylate, and sodium polystyrene sulfonate, and optionally includes one or more of sodium carboxymethyl cellulose and sodium alginate.

[0065] In some embodiments, the polymer comprises sodium carboxymethylcellulose. In some embodiments, the polymer comprises sodium alginate. In some embodiments, the polymer comprises sodium carboxymethylcellulose and sodium alginate. In some embodiments, the polymer comprises sodium polyacrylate. In some embodiments, the polymer comprises sodium perfluorosulfonic acid resin.

[0066] Polymer coatings containing the aforementioned polymers all exhibit high sodium ion conductivity. By altering the solvation structure of sodium ions in the electrolyte, they reduce the amount of free electrolyte solvent at the interface between sodium metal and the separator, thereby minimizing side reactions between the electrolyte and sodium metal and improving the battery's cycling and storage performance. Polymers containing sodium carboxymethyl cellulose or sodium alginate can further enhance the battery's cycling and storage performance.

[0067] In some embodiments, the thickness of the polymer coating is 15 nm to 1500 nm, optionally 50 nm to 1000 nm. In some embodiments, the thickness of the polymer coating can be 15 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, 1000 nm, 1150 nm, 1200 nm, 1250 nm, 1300 nm, 1350 nm, 1400 nm, 1450 nm, 1500 nm, or a value in a range consisting of any two of the above points.

[0068] Controlling the polymer coating thickness to 15nm to 1500nm can both avoid or reduce the inadequate protection of the sodium metal phase in the negative electrode due to a thin coating, and also avoid or reduce the adverse effects of an increase in battery internal resistance due to an excessively thick coating. Further controlling the polymer coating thickness to 50nm to 1000nm can further improve the battery's cycling and storage performance.

[0069] In some embodiments, the polymer coating further comprises a surfactant additive, wherein the surfactant additive comprises one or more of sodium lauryl sulfate, sodium polydipropylene glycol sulfonate, and polyethylene glycol, and optionally sodium polydipropylene glycol sulfonate.

[0070] The addition of surfactant additives is beneficial to improving the wettability between the polymer coating and sodium metal, so that sodium ions can be more evenly deposited on the surface of the negative electrode current collector, reducing the generation of sodium dendrites and avoiding internal short circuits in the battery. It is also beneficial to improving the cycle performance and storage performance of sodium metal batteries.

[0071] In some embodiments, the mass content of the surfactant additive is 0.05% to 5%, optionally 0.2% to 3%, based on the total mass of the polymer coating. In some embodiments, the mass content of the surfactant additive is 0.05%, 0.1%, 0.15%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5%, or a value in a range consisting of any two of the above values, based on the total mass of the polymer coating.

[0072] Controlling the surfactant content to 0.05% to 5% can avoid or reduce the technical effect of not improving the wettability between the polymer coating and the sodium metal due to a low surfactant content, and can also avoid or reduce the increase in battery impedance and the resulting decrease in battery performance due to a high surfactant content. Further controlling the surfactant content to 0.2% to 3% can further improve the battery's cycling and storage performance.

[0073] In some embodiments, the polymer coating further comprises a reinforcing component comprising one or more of polyvinylidene fluoride, styrene-butadiene copolymer, polyimide, polyacrylonitrile, polyacrylamide, polymethyl methacrylate, nitrile rubber and polyurethane, optionally comprising styrene-butadiene copolymer.

[0074] Adding reinforcing components to the polymer coating is beneficial to improving the mechanical strength and flexibility of the composite diaphragm membrane and expanding the application of the composite isolation membrane.

[0075] In some embodiments, the weight content of the reinforcing component is 0.01% to 50%, optionally 0.05% to 10%, based on the total weight of the polymer coating. In some embodiments, the weight content of the reinforcing component is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 4%, 5%, 6%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or a value in a range consisting of any two of the above points, based on the total weight of the polymer coating.

[0076] Controlling the weight content of the reinforcing component to 0.01% to 50% can avoid or reduce the inability to improve the performance of the composite separator due to a low weight content of the reinforcing component, and can also avoid or reduce the increase in battery impedance and the resulting decrease in battery performance due to a high weight content of the reinforcing component. Further controlling the weight content of the reinforcing component to 0.05% to 10% can further improve the cycling performance and storage performance of the battery.

[0077] In some embodiments, the separator substrate includes one or more of polyethylene, polypropylene, polyester, cellulose, polyimide, polyamide, spandex fiber, and aramid fiber, and optionally includes polyethylene.

[0078] In some embodiments, the separator substrate comprises polyethylene. In some embodiments, the separator substrate comprises polypropylene. In some embodiments, the separator substrate comprises polyamide. In some embodiments, the separator substrate comprises aramid fiber.

[0079] The sources of isolation membrane substrates are wide, and all of the above isolation membrane substrates can be used in combination with polymer coatings to improve battery performance.

[0080] [Positive electrode]

[0081] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer formed on at least a portion of the surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, which may include at least one of a layered transition metal oxide, a polyanionic compound, and a Prussian blue compound.

[0082] The transition metal in the layered transition metal oxide can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Optionally, the layered transition metal oxide is, for example, NaxMO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr, and Cu, and 0<x≤1.

[0083] Polyanionic compounds can be metal ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The metal ion can be selected from sodium ion, lithium ion, potassium ion, and zinc ion; the transition metal can be selected from at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be selected from at least one of P, S, and Si; n represents (YO4) n- valence.

[0084] Prussian blue compounds can be compounds containing sodium ions, transition metal ions, and cyanide ions (CN-). The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.

[0085] The positive electrode active material layer may further include a conductive agent to improve the conductivity of the positive electrode. The conductive agent may be selected from one or more of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers.

[0086] The positive electrode active material layer may further include a binder to firmly bond the positive electrode active material and optional conductive agent to the positive electrode current collector. The binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA), and carboxymethyl chitosan (CMCS).

[0087] The positive electrode current collector can be a conductive carbon sheet, metal foil, carbon-coated metal foil, porous metal plate, or a composite current collector. The conductive carbon material of the conductive carbon sheet can be selected from one or more of Super P, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers. The metal material of the metal foil, carbon-coated metal foil, and porous metal plate can each be independently selected from at least one of copper, aluminum, nickel, and stainless steel. The composite current collector can be a composite of metal foil and a polymer-based film.

[0088] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0089] [Negative electrode]

[0090] The negative electrode plate may only include a negative electrode current collector without including a negative electrode active material. The negative electrode plate may also be formed by pre-depositing a metal phase on the negative electrode current collector.

[0091] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil or copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0092] In some embodiments, the negative electrode plate includes a negative electrode current collector and a primer layer disposed on at least one surface of the negative electrode current collector, wherein the primer layer includes one or more of carbon nanotubes, graphite, graphene, carbon black, aluminum oxide, silver composite carbon nanoparticles, and tin composite carbon nanoparticles.

[0093] As used herein, the term "carbon nanotube" refers to a seamless hollow cylinder formed by rolling up a single or multiple layers of graphene, with a diameter less than 100 nm and a length greater than 100 nm. Examples of carbon nanotubes include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

[0094] The above-mentioned primer layer not only has excellent conductivity, but also facilitates the uniform deposition of metal ions on the surface of the current collector, thereby improving the cycle performance and safety of the battery.

[0095] In some embodiments, the basecoat layer has an areal density of 0.5 g / m 2 ~35g / m 2 .

[0096] In some embodiments, the surface density of the base coating can be 0.5 g / m 2 , 1g / m 2 , 2g / m 2 , 3g / m 2 , 4g / m 2 , 5g / m 2 , 10g / m 2 , 15g / m 2 , 20g / m 2 , 25g / m 2 , 30g / m 2 , 35g / m 2 , or a value in the range formed by any two of the above points.

[0097] Surface density is 5g / m 2 ~50g / m 2 The undercoat layer is beneficial to the uniform distribution of nucleation sites and promotes the uniform deposition of metal without affecting the transport behavior of electrons.

[0098] In some embodiments, the primer layer has a thickness of 0.2 μm to 50 μm.

[0099] In some embodiments, the thickness of the primer layer may be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, or a value in a range consisting of any two of the above points.

[0100] Controlling the thickness of the base coating to be 2 μm to 100 μm can provide enough nucleation sites to facilitate uniform deposition of metal ions and inhibit dendrites.

[0101] [Electrolytes]

[0102] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0103] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0104] In some embodiments, the electrolyte salt may be selected from at least one of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, and sodium chloride.

[0105] In some embodiments, the electrolyte contains an ester solvent, and the ester solvent contains at least one selected from ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, and fluoroethylene carbonate.

[0106] In some embodiments, the electrolyte contains an ether solvent, and the ether solvent includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyltetrahydrofuran, diphenyl ether and crown ether, and optionally includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0107] Ether solvents possess superior molecular anti-reduction properties, promoting the formation of a stable solid electrolyte interface on the sodium metal surface and reducing side reactions during battery cycling. The combination of a composite separator and an ether solvent simultaneously protects the sodium metal phase in the negative electrode through the polymer coating and stabilizes the formation of a solid electrolyte interface, significantly reducing side reactions and improving battery performance. Ether solvents including one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether can further enhance the battery's cycling and storage performance.

[0108] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0109] [Secondary battery]

[0110] A secondary battery includes a negative electrode sheet, an electrolyte, and a composite separator in some embodiments.

[0111] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 is an example of a square-structured battery cell 5 , and FIG2 is an exploded view of the battery cell 5 .

[0112] In some embodiments, the secondary battery further includes a positive electrode sheet.

[0113] In some embodiments, the secondary battery includes at least one of a lithium battery and a sodium battery.

[0114] In some embodiments, the secondary battery includes at least one of a potassium battery, a magnesium battery, and a zinc battery.

[0115] In some embodiments, the secondary battery is a negative electrode-less sodium battery.

[0116] Anode-free sodium secondary batteries do not pre-deposit negative electrode active materials and only contain anode current collectors. During the first charge, sodium ions gain electrons at the cathode side and metallic sodium is deposited on the current collector surface to form a sodium metal phase. During discharge, the metallic sodium can be converted into sodium ions and returned to the positive electrode, achieving cyclic charge and discharge. Compared to other sodium secondary batteries, anode-free sodium secondary batteries can achieve higher energy density because they are not restricted by negative electrode materials. Moreover, while maintaining the battery's high electrochemical performance, they can shorten the battery production cycle, reduce the battery's manufacturing cost, and greatly improve production efficiency.

[0117] In some embodiments, the CB value of the negative electrode-free sodium secondary battery is less than or equal to 0.1.

[0118] The CB value is the capacity per unit area of ​​the negative electrode in a secondary battery divided by the capacity per unit area of ​​the positive electrode. Since a battery without a negative electrode contains no negative active material, the capacity per unit area of ​​the negative electrode is relatively small, and the CB value of a secondary battery is less than or equal to 0.1.

[0119] In some embodiments, referring to FIG2 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0120] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0121] Figure 3 shows an example battery module 4. Referring to Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.

[0122] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0123] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0124] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0125] [Electrical devices]

[0126] In one embodiment of the present application, an electric device is provided, comprising at least one of a secondary battery according to any embodiment, a battery module according to any embodiment, or a battery pack according to any embodiment.

[0127] The electrical device includes at least one of the secondary batteries, battery modules, or battery packs provided in this application. The secondary batteries, battery modules, or battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0128] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0129] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0130] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0131] Example

[0132] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0133] 1. Preparation method

[0134] Example 1

[0135] 1) Preparation of composite isolation membrane

[0136] Sodium carboxymethyl cellulose (CMC) was dissolved in deionized water to produce a polymer slurry. This polymer slurry was evenly applied to one surface of a polyethylene (PE) separator substrate using a doctor blade to form a polymer coating. After coating, the coating was transferred to a vacuum drying oven for drying, oven drying, and slitting to produce a composite separator. The polymer coating had a thickness of 200 nm, and the sodium ion conductivity of the composite separator was 0.53 mS / cm.

[0137] 2) Preparation of positive electrode sheet

[0138] 10wt% polyvinylidene fluoride binder was fully dissolved in N-methylpyrrolidone. 10wt% carbon black conductive agent and 80wt% Na4Fe3(PO4)2P2O7 positive electrode active material were added and stirred to form a positive electrode slurry. The slurry was evenly coated on the surface of the current collector aluminum foil to form a positive electrode film. The film was then transferred to a vacuum drying oven for complete drying. The dried electrode was then roll-pressed and punched to form the positive electrode sheet.

[0139] 3) Preparation of negative electrode sheet

[0140] Aluminum foil is used as the negative electrode current collector for slitting and die-cutting to prepare negative electrode sheets without a negative electrode film layer.

[0141] 4) Electrolyte

[0142] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium hexafluorophosphate NaPF6 was dissolved in an organic solvent, ethylene glycol dimethyl ether (DME), and stirred evenly to obtain an electrolyte with a sodium salt concentration of 1 mol / L.

[0143] 5) Preparation of batteries

[0144] The positive electrode sheet, composite separator, and negative electrode sheet were stacked in order, with the composite separator positioned between the positive and negative electrode sheets to provide isolation, and the polymer coating within the composite separator positioned on the negative electrode side. Tabs were welded to the bare cell, which was then encased in aluminum-plastic film and baked at 80°C to remove moisture. The electrolyte was then injected and sealed to produce an uncharged battery. The uncharged battery then underwent a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the negative-electrode-free sodium secondary battery product of Example 1.

[0145] Example 2

[0146] 1) Preparation of composite isolation membrane

[0147] Sodium carboxymethylcellulose (CMC) and sodium polydisulfide-dipropanesulfonate were dissolved in deionized water to produce a polymer slurry. This polymer slurry was evenly applied to one surface of a polyethylene (PE) separator substrate using a doctor blade to form a polymer coating. After coating, the coating was transferred to a vacuum drying oven for drying, oven drying, and slitting to produce a composite separator. The polymer coating had a thickness of 200 nm and a sodium polydisulfide content of 0.5% based on the total weight of the polymer coating. The composite separator had a sodium ion conductivity of 0.53 mS / cm.

[0148] 2) Preparation of positive electrode sheet

[0149] 10wt% polyvinylidene fluoride binder was fully dissolved in N-methylpyrrolidone. 10wt% carbon black conductive agent and 80wt% Na4Fe3(PO4)2P2O7 positive electrode active material were added and stirred to form a positive electrode slurry. The slurry was evenly coated on the surface of the current collector aluminum foil to form a positive electrode film. The film was then transferred to a vacuum drying oven for complete drying. The dried electrode was then roll-pressed and punched to form the positive electrode sheet.

[0150] 3) Preparation of negative electrode sheet

[0151] Aluminum foil is used as the negative electrode current collector for slitting and die-cutting to prepare negative electrode sheets without a negative electrode film layer.

[0152] 4) Electrolyte

[0153] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium hexafluorophosphate NaPF6 was dissolved in an organic solvent, ethylene glycol dimethyl ether (DME), and stirred evenly to obtain an electrolyte with a sodium salt concentration of 1 mol / L.

[0154] 5) Preparation of batteries

[0155] The positive electrode sheet, composite separator, and negative electrode sheet are stacked in order, with the composite separator positioned between the positive and negative electrode sheets to act as an insulator, and the polymer coating in the composite separator positioned on the negative electrode side. Tabs are welded to the bare cell, which is then encased in aluminum-plastic film and baked at 80°C to remove moisture. The electrolyte is then injected and sealed to produce an uncharged battery. The uncharged battery then undergoes a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the negative-electrode-free sodium secondary battery product of Example 2.

[0156] Examples 3 to 24

[0157] The preparation methods of the batteries of Examples 3 to 24 are similar to those of the battery of Example 2, but the preparation parameters of the composite separator and the secondary battery are adjusted. The specific parameters are shown in Tables 1 and 2.

[0158] Example 25

[0159] 1) Preparation of composite isolation membrane

[0160] Sodium carboxymethylcellulose (CMC) and sodium polydisulfide-dipropanesulfonate were dissolved in deionized water to produce a polymer slurry. This polymer slurry was evenly applied to one surface of a polyethylene (PE) separator substrate using a doctor blade to form a polymer coating. After coating, the coating was transferred to a vacuum drying oven for drying, oven drying, and slitting to produce a composite separator. The polymer coating had a thickness of 200 nm and a sodium polydisulfide content of 0.5% based on the total weight of the polymer coating. The composite separator had a sodium ion conductivity of 0.53 mS / cm.

[0161] 2) Preparation of positive electrode sheet

[0162] 10wt% polyvinylidene fluoride binder was fully dissolved in N-methylpyrrolidone. 10wt% carbon black conductive agent and 80wt% Na4Fe3(PO4)2P2O7 positive electrode active material were added and stirred to form a positive electrode slurry. The slurry was evenly coated on the surface of the current collector aluminum foil to form a positive electrode film. The film was then transferred to a vacuum drying oven for complete drying. The dried electrode was then roll-pressed and punched to form the positive electrode sheet.

[0163] 3) Preparation of negative electrode sheet

[0164] Weigh 5g of single-walled carbon nanotubes and dissolve them in deionized water. Then, ultrasonically disperse them to prepare a slurry. The slurry is coated on the aluminum foil negative electrode current collector to prepare a primer layer. The slurry is then transferred to a vacuum drying oven for complete drying. The negative electrode sheet without a negative electrode structure is then cut and die-cut. The surface density of the primer layer is 1g / m 2 .

[0165] 4) Electrolyte

[0166] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium hexafluorophosphate NaPF6 was dissolved in an organic solvent, ethylene glycol dimethyl ether (DME), and stirred evenly to obtain an electrolyte with a sodium salt concentration of 1 mol / L.

[0167] 5) Preparation of batteries

[0168] The positive electrode sheet, composite separator, and negative electrode sheet were stacked in order, with the composite separator positioned between the positive and negative electrodes to provide insulation. The polymer coating within the composite separator was located on the negative electrode side. Tabs were welded to the bare cell and encased in aluminum-plastic film. The cells were baked at 80°C to remove moisture, then electrolyte was injected and sealed to produce an uncharged battery. The uncharged battery then underwent a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the sodium secondary battery product of Example 25.

[0169] Example 26

[0170] The preparation method of the battery of Example 26 is similar to that of the battery of Example 25, but the primer layer on the negative electrode current collector is adjusted. The specific parameters are shown in Tables 1 and 2.

[0171] Comparative Example 1

[0172] The battery preparation method in Comparative Example 1 is basically similar to that in Example 1, but the composite separator only includes a separator substrate and does not include a polymer coating. Specific parameters are shown in Tables 1 and 2.

[0173] Comparative Example 2

[0174] The preparation method of the battery of Comparative Example 2 is similar to that of the battery of Comparative Example 1, but the type of solvent in the electrolyte is adjusted. The specific parameters are shown in Tables 1 and 2.

[0175] Comparative Example 3

[0176] 1) Preparation of composite isolation membrane

[0177] Polyvinylidene fluoride (PVDF) was dissolved in deionized water to produce a polymer slurry. This polymer slurry was evenly applied to one surface of a polyethylene (PE) separator substrate using a doctor blade to form a polymer coating. After coating, the coating was transferred to a vacuum drying oven for drying, oven drying, and slitting to produce a composite separator. The polymer coating had a thickness of 200 nm, and the sodium ion conductivity of the composite separator was 0.11 mS / cm.

[0178] 2) Preparation of positive electrode sheet

[0179] 10wt% polyvinylidene fluoride binder was fully dissolved in N-methylpyrrolidone. 10wt% carbon black conductive agent and 80wt% Na4Fe3(PO4)2P2O7 positive electrode active material were added and stirred to form a positive electrode slurry. The slurry was evenly coated on the surface of the current collector aluminum foil to form a positive electrode film. The film was then transferred to a vacuum drying oven for complete drying. The dried electrode was then roll-pressed and punched to form the positive electrode sheet.

[0180] 3) Preparation of negative electrode sheet

[0181] The aluminum foil current collector is cut and die-cut to prepare a negative electrode sheet without a negative electrode film layer.

[0182] 4) Electrolyte

[0183] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium hexafluorophosphate NaPF6 was dissolved in an organic solvent, ethylene glycol dimethyl ether (DME), and stirred evenly to obtain an electrolyte with a sodium salt concentration of 1.0 mol / L.

[0184] 5) Preparation of batteries

[0185] The positive electrode sheet, composite separator, and negative electrode sheet were stacked in order, with the composite separator positioned between the positive and negative electrodes to provide insulation. The polymer coating within the composite separator was located on the negative electrode side. Tabs were welded to the bare cell, which was then encased in aluminum-plastic film and baked at 80°C to remove moisture. The electrolyte was then injected and sealed to produce an uncharged battery. The uncharged battery then underwent a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the negative-electrode-free sodium secondary battery product of Comparative Example 3.

[0186] Comparative Example 4

[0187] The preparation method of the battery of Comparative Example 4 is similar to that of the battery of Comparative Example 3, but the type of solvent in the electrolyte is adjusted. The specific parameters are shown in Tables 1 and 2.

[0188] 2. Performance Testing

[0189] 1. Composite isolation membrane

[0190] 1) Sodium ion conductivity test

[0191] Taking Example 1 as an example, a symmetrical battery is used to test the sodium ion conductivity of the composite isolation membrane. The preparation process of the symmetrical battery is similar to that of the battery in Example 1, except that its negative electrode plate is coated with a hard carbon material. At the same time, the battery is stacked in the form of a negative electrode plate, an isolation membrane, and a negative electrode plate. The calculation formula for sodium ion conductivity is: σ = l / (K·S)*10, where σ is the sodium ion conductivity of the composite isolation membrane, in mS / cm; l is the thickness of a layer of composite isolation membrane, in m; S is the effective area of ​​the composite isolation membrane in the test battery, in m 2 K is the bulk resistance of the electrolyte in a composite separator, measured in Ω. The cell impedance was measured using a French Bio-Logic VMP3B electrochemical workstation to determine the bulk resistance of the composite separator. The testing procedures for the comparative example and other examples were the same as above.

[0192] 2. Battery performance test

[0193] 1) Cyclic performance test

[0194] The cycling performance test process is as follows: at 25°C, charge at a constant current of 1C to 3.7V, then charge at a constant voltage of 3.7V until the current drops to 0.05C, and then discharge at a constant current of 1C to 2.5V to obtain the initial capacity (C0). Repeat this charge and discharge process for the nth cycle, and obtain the discharge capacity of the sodium ion battery after n cycles, which is recorded as Cdn. The process capacity of the battery after the 100th cycle (C100) is recorded. The capacity retention rate after 100 cycles = C100 / C1×100%. The testing process of the comparative example and other examples is the same as above.

[0195] 2) Storage performance test

[0196] The storage performance test process is as follows: After the prepared full battery is left at rest for 4 hours at 25°C, the battery is charged to 3.7V at a constant current of 0.33C. Then, the battery is charged at a constant voltage of 3.7V until the current drops to 0.05C. Then, the battery is discharged to 2.5V at a constant current of 0.33C to obtain the initial discharge capacity D1. The battery is stored in a constant temperature environment at 25°C for 60 days, and the above test steps are repeated to obtain the discharge capacity D2. The battery capacity retention rate after 60 days of storage = D2 / D1 × 100%. The testing process for the comparative example and other examples is the same as above.

[0197] 3. Analysis of test results of various embodiments and comparative examples

[0198] Batteries of various examples and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Tables 1 and 2 below.

[0199] Table 1

[0200] Table 2

[0201] The above results indicate that the composite separators in Examples 1-26 comprise a separator substrate and a polymer coating positioned on one side of the separator substrate, and exhibit ionic conductivities ranging from 0.1 mS / cm to 6 mS / cm. A comparison of Examples 1-23 with Comparative Examples 1 and 4, and Example 24 with Comparative Examples 2-3, demonstrates that providing a polymer coating on one side of the separator substrate and controlling the ionic conductivity of the composite separator to 0.3 mS / cm to 1 mS / cm improves the capacity retention and storage performance of the battery after 100 cycles, broadening its applications.

[0202] Comparison of Examples 1 to 23 with Comparative Examples 1 and 4 shows that polymer coatings containing -COONa groups or -SOONa groups are beneficial for improving the capacity retention and storage performance of the battery after 100 cycles. Comparison of Examples 2 and 15 with Comparative Examples 14 and 16 shows that, compared with polymer coatings containing -SOONa groups, polymer coatings containing -COONa groups are beneficial for further improving the capacity retention and storage performance of the battery after 100 cycles.

[0203] From the comparison between Examples 1 to 23 and Comparative Examples 1 and 4, it can be seen that the polymer in the polymer coating includes sodium carboxymethyl cellulose, sodium polyacrylate, sodium alginate or sodium perfluorosulfonic acid resin, which is beneficial to improving the capacity retention rate and storage performance of the battery after 100 cycles.

[0204] Comparison of Examples 2 to 6 with Examples 7 to 8 shows that controlling the thickness of the polymer coating to 15 nm to 1500 nm is beneficial for further improving the capacity retention and storage performance of the battery after 100 cycles. Comparison of Examples 2, 4 to 5 with Examples 3 and 6 shows that controlling the thickness of the polymer coating to 50 nm to 1000 nm is beneficial for further significantly improving the capacity retention and storage performance of the battery after 100 cycles.

[0205] From the comparison of Examples 9 to 13, 17 to 18 with Comparative Example 1, it can be seen that the polymer coating also includes a surfactant additive, and the surfactant additive includes sodium lauryl sulfate, sodium polydisulfide dipropane sulfonate or polyethylene glycol, which is beneficial to improving the capacity retention rate and storage performance of the battery after 100 cycles.

[0206] Comparison of Examples 2, 9 to 13 with Comparative Example 1 shows that controlling the mass content of the surfactant additive to 0.05% to 5% is beneficial for improving the capacity retention rate and storage performance of the battery after 100 cycles. Comparison of Examples 2, 10 to 12 with Examples 9 and 13 shows that controlling the mass content of the surfactant additive to 0.2% to 3% is beneficial for further improving the capacity retention rate and storage performance of the battery after 100 cycles.

[0207] From the comparison between Examples 20 to 21 and Example 2, it can be seen that the polymer coating also includes a reinforcing component, which includes polyvinylidene fluoride or styrene-butadiene copolymer, which is beneficial to further improve the capacity retention rate and storage performance of the battery after 100 cycles.

[0208] From the comparison of Examples 2, 22 to 23 with Example 24, it can be seen that, compared with the case where the solvent in the electrolyte is selected from dimethyl carbonate, the case where the solvent in the electrolyte is selected from ethylene glycol dimethyl ether, ethylene glycol diethyl ether or tetrahydrofuran is more conducive to improving the capacity retention rate and storage performance of the battery after 100 cycles. From the comparison of Examples 2, 22 and Example 23, it can be seen that, compared with the case where the solvent in the electrolyte is selected from tetrahydrofuran, the case where the solvent in the electrolyte is selected from ethylene glycol dimethyl ether or ethylene glycol diethyl ether is more conducive to further improving the capacity retention rate and storage performance of the battery after 100 cycles.

[0209] From the comparison between Examples 25 to 26 and Example 2, it can be seen that providing a single-walled carbon nanotube primer layer or a graphene primer layer on the negative electrode current collector is beneficial to improving the capacity retention rate and storage performance of the battery after 100 cycles.

[0210] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A composite isolation membrane, It is characterized in that The composite isolation membrane comprises an isolation membrane substrate and a polymer coating located on one side of the isolation membrane substrate. The sodium ion conductivity of the composite isolation membrane is 0.3 mS / cm to 1 mS / cm.

2. The composite isolation membrane according to claim 1, It is characterized in that The polymer coating includes at least one of a polymer containing sodium carboxylate groups and / or sodium sulfonate groups, the polymer being conductive to metallic sodium ions.

3. The composite isolation membrane according to claim 1 or 2, It is characterized in that The polymer includes one or more of sodium carboxymethyl cellulose, sodium polyacrylate, sodium alginate, sodium perfluorosulfonic acid resin, sodium polymethacrylate and sodium polystyrene sulfonate, and optionally includes one or more of sodium carboxymethyl cellulose and sodium alginate.

4. The composite isolation membrane according to any one of claims 1 to 3, It is characterized in that The thickness of the polymer coating is 15 nm to 1500 nm, and can be optionally 50 nm to 1000 nm.

5. The composite isolation membrane according to any one of claims 1 to 4, It is characterized in that The polymer coating further comprises a surfactant additive, wherein the surfactant additive comprises one or more of sodium dodecyl sulfate, sodium poly(dipropylene glycol) sulfonate and polyethylene glycol, and optionally sodium poly(dipropylene glycol) sulfonate.

6. The composite isolation membrane according to claim 5, It is characterized in that Based on the total mass of the polymer coating, the mass content of the surfactant additive is 0.05% to 5%, and can be optionally 0.2% to 3%.

7. The composite isolation membrane according to any one of claims 1 to 6, It is characterized in that The polymer coating further comprises a reinforcing component, which comprises one or more of polyvinylidene fluoride, styrene-butadiene copolymer, polyimide, polyacrylonitrile, polyacrylamide, polymethyl methacrylate, nitrile rubber and polyurethane, and optionally comprises styrene-butadiene copolymer.

8. The composite isolation membrane according to claim 7, It is characterized in that Based on the total mass of the polymer coating, the mass content of the reinforcing component is 0.01% to 50%, and optionally 0.05% to 10%.

9. The composite isolation membrane according to any one of claims 1 to 8, It is characterized in that The isolation film substrate includes one or more of polyethylene, polypropylene, polyester, cellulose, polyimide, polyamide, spandex fiber and aramid fiber, and optionally includes polyethylene.

10. A sodium secondary battery, It is characterized in that It comprises a negative electrode plate, an electrolyte and a composite isolation membrane according to any one of claims 1 to 9, wherein the polymer coating of the composite isolation membrane is located on the negative electrode plate side.

11. The sodium secondary battery according to claim 10, It is characterized in that The secondary battery is a negative electrode-free sodium secondary battery.

12. The sodium secondary battery according to claim 10 or 11, It is characterized in that The electrolyte includes an ether solvent, and the ether solvent includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyltetrahydrofuran, diphenyl ether and crown ether, and optionally includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

13. The sodium secondary battery according to any one of claims 10 to 12, It is characterized in that The negative electrode plate includes a negative electrode current collector and a primer layer disposed on at least one surface of the negative electrode current collector, wherein the primer layer includes one or more of carbon nanotubes, graphite, graphene, silver composite carbon nanoparticles, and tin composite carbon nanoparticles.

14. The sodium secondary battery according to claim 13, It is characterized in that The surface density of the primer layer is 0.5 g / m 2 ~35g / m 2 .

15. The sodium secondary battery according to claim 13 or 14, It is characterized in that The thickness of the primer layer is 0.2 μm to 50 μm.

16. An electrical device, It is characterized in that A sodium secondary battery comprising the sodium secondary battery according to any one of claims 10 to 15.